ЕФЕКТИВНІСТЬ РОБОЧИХ РЕЖИМІВ АСИНХРОННИХ ДВИГУНІВ ПОРШНЕВИХ КОМПРЕСОРІВ ПРИ ЧАСТОТНОМУ РЕГУЛЮВАННІ - Бібік, О.В.; Головань, І.В.; Попович, О.М.; Шуруб, Ю.В. (Інститут електродинаміки НАН України, Київ, 2020)
The influence of periodic load on pulsations of electromagnetic torque and rotational speed, the losses and the efficiency of frequency-controlled induction motors for single-cylinder piston compressors are investigated using computer modeling. The region of critical reduction of motor efficiency when changing the frequency and supply voltage and the loading degree are determined using the criterion of heavy quasi-static regimes. References 16, figures 7, tables 2.